2023
DOI: 10.1037/ppm0000427
|View full text |Cite
|
Sign up to set email alerts
|

A moderated mediation model of the relationship between passive social network usages and life satisfaction.

Abstract: This study examined whether the adverse link between passive social network usage (PSNU) and life satisfaction was mediated by both envy and self-esteem (serial- and parallel-mediation models) based on social comparison theory (Festinger, 1954). In addition, according to social role theory (Eagly, 1987), sex was used as a moderator variable to moderate several recommended pathways related to envy. A total of 590 Vietnamese university students voluntarily participated in this survey study. The findings revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Yue et al [ 50 ], in their research exploring social media browsing and unhealthy social comparison in Wuhan City, China, found that passive use of social media transfers its significant impact on life satisfaction by influencing the wellbeing of citizens. In a similar vein Nguyen and Cheng [ 51 ], while testing a moderated mediation model, demonstrated that the way individuals use social media has a significant impact on their life satisfaction. Considering the evidence outlined above we hypothesise that:…”
Section: Literature Reviewmentioning
confidence: 89%
“…Yue et al [ 50 ], in their research exploring social media browsing and unhealthy social comparison in Wuhan City, China, found that passive use of social media transfers its significant impact on life satisfaction by influencing the wellbeing of citizens. In a similar vein Nguyen and Cheng [ 51 ], while testing a moderated mediation model, demonstrated that the way individuals use social media has a significant impact on their life satisfaction. Considering the evidence outlined above we hypothesise that:…”
Section: Literature Reviewmentioning
confidence: 89%